Suppression of Ripe Rot on ‘Zesy002’ Kiwifruit with Commercial Agrochemicals - Yong Ho Shin; Magda Ledesma; Sonia Whitman; Joy Tyson; Birgit Zange; Ki Deok Kim; Yong Chull Jeun (The Plant Pathology Journal, 2021)
Ripe rot caused by Botryosphaeria dothidea is one of the serious diseases of postharvest kiwifruit. In order to control ripe rot on Actinidia chinensis cultivar ‘Zesy002’, several commercial agrofungicides were selected by an antifungal test on an artificial medium. Furthermore, disease suppression by the selected fungicides was evaluated on the kiwifruit by inoculation with a conidial suspension of B. dothidea. On the artificial media containing boscalid + fludioxonil was shown to be the most effective antifungal activity. However, in the bio-test pyraclostrobin + boscalid and iminoctadine-tris were the most effective agrochemicals on the fruit. On the other hand, the infection structures of B. dothidea on kiwifruit treated with pyraclostrobin + boscalid were observed with a fluorescent microscope. Most of the fungal conidia had not germinated on the kiwifruit treated with the agrochemicals whereas on the untreated fruit the fungal conidia had mostly germinated. Electron microscopy of the fine structures showed morphological changes to the conidia and branch of hyphae on the kiwifruit pre-treated with pyraclostrobin + boscalid, indicating its suppression effect on fungal growth. Based on this observation, it is suggested that ripe rot by B. dothidea may be suppressed through the inhibition of conidial germination on the kiwifruit treated with the agrochemicals.